2009
DOI: 10.1002/ijc.24340
|View full text |Cite
|
Sign up to set email alerts
|

The VE‐cadherin binding domain of fibrinogen induces endothelial barrier permeability and enhances transendothelial migration of malignant breast epithelial cells

Abstract: Fibrin deposition and exudation of plasma fibrinogen (Fg) have long been recognized as hallmarks of inflammation, cardiovascular disease and neoplasia. The Fg-b 15-42 domain binds to the endothelial cell adhesion molecule, VE-cadherin, promoting endothelial cell proliferation, angiogenesis and leukocyte diapedesis. Furthermore, spontaneous blood-borne and lymphatic metastasis of some types of tumor emboli requires plasma fibrin(ogen); however, the molecular mechanisms by which this occurs are poorly understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 44 publications
4
59
0
Order By: Relevance
“…Using transwell insert culture systems, we showed that Fg  15-42 and VEcadherin binding interactions promote endothelial cell barrier permeability (Sahni et al, 2009) (Fig. 6).…”
Section: -42 Induces Endothelial Barrier Permeability Via Ve-cadhermentioning
confidence: 96%
See 4 more Smart Citations
“…Using transwell insert culture systems, we showed that Fg  15-42 and VEcadherin binding interactions promote endothelial cell barrier permeability (Sahni et al, 2009) (Fig. 6).…”
Section: -42 Induces Endothelial Barrier Permeability Via Ve-cadhermentioning
confidence: 96%
“…Although Fg is known for its hemostatic role, we showed that Fg, not fibrin, is a component of the insoluble fibrillar ECM of fibroblasts, alveolar epithelial cells, endothelial cells and breast epithelial cells (Guadiz et al, 1997;Pereira et al, 2002;Sahni et al, 2009;SimpsonHaidaris et al, 2010;Simpson-Haidaris & Sahni, 2010). Upon assembly into matrix fibrils, Fg undergoes conformational changes exposing the cryptic  15-42 epitope in the absence of thrombin cleavage or covalent crosslinking (Guadiz et al, 1997;Simpson-Haidaris & Sahni, 2010).…”
Section: Fibrinogen Is An Extracellular Matrix Proteinmentioning
confidence: 98%
See 3 more Smart Citations